Colony-stimulating factor-1-induced AIF1 expression in tumor-associated macrophages enhances the progression of hepatocellular carcinoma. (2nd September 2017) - Cai, Hao; Zhu, Xiao-Dong; Ao, Jian-Yang; Ye, Bo-Gen; Zhang, Yuan-Yuan; Chai, Zong-Tao; Wang, Cheng-Hao; Shi, Wen-Kai; Cao, Man-Qing; Li, Xiao-Long; Sun, Hui-Chuan
ABSTRACT: M2-polarized (alternatively activated) macrophages play an important role in the progression of hepatocellular carcinoma (HCC). Allograft inflammatory factor 1 (AIF1) is overexpressed in M2-polarized macrophages. This study explored the role of AIF1 in tumor-associated macrophages in HCC. Macrophages were stimulated with colony-stimulating factor 1 (CSF1) to characterize the regulatory pathway of AIF1 in macrophages. The chromatin immunoprecipitation and luciferase reporter gene assay were conducted to examine transcription factors associated with AIF1 expression. AIF1 was down or upregulated, and the effects on tumor progression were evaluated by using in vitro and in vivo co-culture systems. A cytokine array was performed to screen the downstream functional components of AIF1. Tumor tissue from 206 patients with HCC were used to explore the clinical significance of AIF1. AIF1 induced a M2-like phenotype of macrophages. By facilitating the binding of c-Jun to the promoter of AIF1, CSF1 secreted from hepatoma cells increased AIF1 expression through the CSF1R-MEK1/2-Erk1/2-c-Jun axis. AIF1 expressed in macrophages promoted the migration of hepatoma cells in co-culture system of RAW264.7 and Hepa1-6 and tumor growth in an animal model. The cytokine array showed that CXCL16 was increased in RAW264.7 cells with overexpressed AIF1, leading to enhanced tumor cell migration. In human HCC tissue, AIF1-positive macrophages in the adjacent microenvironment was associated with microvascular invasion and advanced TNM stages and with patients' overall and disease-free survival ( p = 0.002 for both). AIF1 expression in macrophages plays a pivotal role in the interaction between macrophages and hepatoma cells.